(untitled) (Annals of Medical Research, 2025)
Aim: Human immunodeficiency virus (HIV) can cause tumoral changes in immune cells and lead to the development of AIDS-defining malignancies. As malignancies in HIV-infected individuals tend to be quite aggressive with a worse prognosis, making a definitive and early decision about HIV-related malignancies is very important. Therefore, the aim of this study was to examine HIV-related malignancies in HIV-positive patients and evaluate F18-FDG PET/CT results. Materials and Methods: This single-centre, retrospective study was conducted on adult patients with HIV infection at a university hospital between January 2018 and December 2022. The demographic data, medication use, viral loads, and F18-FDG PET/CT results of the patients were accessed retrospectively from the automated hospital records system and patient files. F18-FDG PET/CT images of patients were evaluated for those with suspicion of cancer and staging of cancer. Results: The study included 254 patients with median age (IQR) 33 (20) years, male sex: 81.9%. Malignancy was diagnosed in 3.1% (8/254) of HIV-positive patients. Non-Hodgkin lymphoma and Kaposi’s sarcoma were the most common cancers. F18-FDG PET/CT was performed in 3.5% (9/254) of patients, of which 2.76% (7/254) had findings suggestive of malignancy. As a result of the biopsy, malignancy was detected in five of these patients, and HIV-related lymphadenopathy was detected in two. In two patients, there were no F18-FDG PET/CT imaging findings suggestive of malignancy. Conclusion: F18-FDG PET/CT can be used in the evaluation of HIV-infected patients with suspected malignancy.